Staphylococcus epidermidis biofilms undergo metabolic and matrix remodeling under nitrosative stress - Oliveira, Ana S.; Saraiva, Lígia M.; Carvalho, Sandra M. (Frontiers in Cellular and Infection Microbiology, 2023)
SStaphylococcus epidermidis is a commensal skin bacterium that forms host- and antibiotic-resistant biofilms that are a major cause of implant-associated infections. Most research has focused on studying the responses to host-imposed stresses on planktonic bacteria. In this work, we address the open question on how S. epidermidis thrives on toxic concentrations of nitric oxide (NO) produced by host innate immune cells during biofilm assembly. We have analyzed alterations of gene expression, metabolism, and matrix structure of biofilms of two clinical isolates of S. epidermidis, namely 1457 and RP62A, formed under NO stress conditions. In both strains, NO lowers the amount of biofilm mass and causes increased production of lactate and decreased acetate excretion from biofilm glucose metabolism. Transcriptional analysis revealed that NO induces icaA, which is directly involved in polysaccharide intercellular adhesion (PIA) production, and genes encoding proteins of the aminosugar pathway (glmM, glmU) that link glycolysis to PIA synthesis. However, the strains seem to have distinct regulatory mechanisms to boost lactate production as NO causes a substantial upregulation of the ldh gene in strain RP62A but not in strain 1457. The analysis of the matrix components of the staphylococcal biofilms, assessed by Confocal Laser Scanning Microscopy (CLSM), showed that NO stimulates PIA and proteins production and interferes with biofilm structure in a strain-dependent manner, but independently of the Ldh level. Thus, NO resistance is attained by remodeling of the staphylococcal matrix architecture and adaptation of main metabolic processes, likely providing in vivo fitness of S. epidermidis biofilms contacting NO-proficient macrophages.